ANALISIS KEMAMPUAN MEMBACA DAN BERHITUNG PADA SISWA KELAS 1 SD MUHAMMADIYAH 17 SURABAYA MELALUI PENGGUNAAN MEDIA BERGAMBAR - Lutfi Rahmawati; Holy Ichda Wahyuni; Kunti Dian Ayu Afiani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
ABSTRACTEducation in Indonesia today needs special attention, many factors cause a lack of interest in students in honing their reading and arithmetic skills. Through the existing problems, this study was written with the aim of analyzing the reading and arithmetic skills of grade 1 students of SD Muhammadiyah 17 Surabaya through the use of picture media. This study uses a descriptive qualitative research method, three stages are used in descriptive analysis, the first is reduction, data display, and verification. The findings of this study show that the reading and arithmetic skills of grade 1 students of SD Muhammadiyah 17 Surabaya through. The use of pictorial media can have a positive impact such as increasing confidence, increasing students' enthusiasm to hone their reading and arithmetic skills, and creating a conducive learning atmosphere so that students are able to understand the material taught happily and easily.